IMPACT OFAPPAREL VARIETIES ON APPAREL PURCHASEINTENTION: AN EMPIRICAL ANALYSISOF MADURAI APPAREL BUYERSThe purpose of this study is to study the impact of apparel varieties on apparel purchasing intention among the apparel buyers of Madurai. The various v - KUMAR S, Mr. AJITH (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to study the impact of apparel varieties on apparel purchasing intention among the apparel buyers of Madurai. The various varieties of apparels men and women wear such as dhotis, shirts, T-shirt,kurtas, jackets, jeans, trousers, cargo pants, track pants, sarees, lehanga choli, chudidhar, pavadaithavani, leggins, salwars, anarkali suits, ethinic wear – women and ethinic wear – men. Self-administered questionnaires were used to collect data from atotal of 400 respondents from Madurai to estimate the apparel purchasing intention level from various varieties of apparels men and women prefer to buy. Results showedthat Level of apparel purchase intension do vary with the characteristics of the respondent such as age and monthly income of the respondents and apparel varieties such as dhotis, T-shirt, jackets, jeans, cargo pants, sarees, lehanga choli, chudidhar, pavadaithavani, leggins, salwars, anarkali suits, and ethinic wear – women are significant and shirts, kurtas, trousers, track pants, and ethinic wear – men are insignificant in the estimation of purchase intention towards apparels.